The Incidence of a Corporation Income Tax in a Growing Economy - Ballentine, J. Gregory (Journal of Political Economy, 1978)
Using a two-sector growth model, this paper examines the incidence of a corporation income tax. While the two-sector static model has provided a fairly precise conclusion as to the incidence of that tax, no such clear conclusion emerges from the growth model. This is because the results are quite sensitive to the precise value of the elasticity of savings with respect to the interest rate. However, one point is clear: Because a tax increase raises the price of investment goods, if savings rates are constant, capitalists must bear a smaller burden than that predicted by the static model.